Unfair contractual terms in standard form contracts under Colombian law (2015)
The content of adhesion contracts is imposed by the proposing party to the adhering party without the possibility of being discussed or modified, thus increasing the risk of altering it's legal balance by the inclusion of unfair terms. For example, in the Colombian legal system different kinds of clauses involving excessive, unfair and unjustified benefits have been identified which benefit the proposing party and that place to the adhering party in a situation of greater weakness. Consequently, the theory of unfair clauses has arisen as a method of repairing this legal imbalance. Different criteria exist for applying this theory in Colombian law, such as in the case of adhesion contracts with consumers or adhesion contracts between employers (or non-consumers).